Feed intake, growth and carcass composition of weaned piglets receiving varying levels of valine and leucine in their diets - frimeyer@gmail.com (University of Pretoria, 2013)
Dissertation (MScAgric (Animal Nutrition))--University of Pretoria, 2011.